Exploring EFL University Students' Challenges in Learning English Writing - Ani Fiani; Dewi Syafitri; Anjasmoro; Nabilah Khairunnisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The present study aimed to explore the multifaceted challenges encountered by undergraduate students in an Indonesian EFL context. This study employed a explanatory sequenced mixed-methods design involving 80 undergraduate students from the English Education Study Program at Universitas PGRI Silampari. Data were collected through close-ended and open-ended questionnaires as well as semi-structured interviews. The findings revealed that students encountered four major categories of challenges. Linguistic difficulties, particularly limited vocabulary, grammatical inaccuracies, and first language interference, were the most frequently reported barriers. Cognitive challenges included difficulties in generating ideas, organizing arguments, and maintaining coherence and cohesion in academic writing. Affective factors, such as writing anxiety, fear of negative evaluation, low self-confidence, and perfectionism, further hindered students' writing performance. In addition, institutional factors, including inconsistent feedback, limited writing practice, inadequate learning resources, and time constraints, contributed to students' writing difficulties. These findings suggest that English academic writing instruction should move beyond a sole emphasis on language accuracy by integrating strategy-based writing instruction, process-oriented pedagogy, emotional support, and sustained opportunities for authentic writing practice. The study contributes to the growing body of EFL writing research by providing a holistic understanding of students' writing challenges and offering pedagogical insights for developing more responsive and learner-centered writing instruction in Indonesian higher education. Keywords: English academic writing, EFL university students, writing challenges